Demystifying Ijaw and European Foreign Trade Relations, in the 19th Century - Abejide, T. S. (NIU Journal of Humanities, 2022)
This paper examines the ways in which the Europeansâ€™ quest for trading ventures across the Atlantic Ocean necessitated their contacts with the Ijaw people along the Niger Delta coast since sixteenth century. It discusses the initial trading transactions between the Europeans and the Ijaws, and specifically casts light on the participation of the Ijaw merchants in the Atlantic Slave Trade. The paper concentrates on the   nineteenth century and the impact the transition from slave trade to legitimate commerce, in particular the palm oil trade, had on the Ijaw and how these changes led to greater involvement by Britain in the region by the end of the century. Using both primary and secondary sources for data collection, this study further explains the fact that palm oil trade lured the Ijaw people into the nexus of capitalist economic system. It argues that the Ijawâ€™s were skillful and blessed with favourable environmental condition required for the growth of palm tree and then, the production of palm oil in large volumes. Their ability to meet the number of volumes required by European merchants brought massive income and revenue to the Ijaw merchants. It concludes that palm oil was the main thrust of foreign relations between the Ijaw people and European traders. Also, the resuscitation of palm oil production by the government is imperative in the Niger Delta region, as it required a re-direction of government policy through proper funding as well as provides low interest loan for the farmers to ensure increase production and supply. It is only when this is done that additional income would accrue to both the local people, government and for the economic development of Nigeria at large. Keywords: Ijaw, Palm Oil, European, Economy, Relations.